Analysis on Students’ Verbal Communication at English Education Study Program of Tomakaka University Mamuju - Fatmawati, Fatmawati (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2024)
This research tries to investigate the Analysis of Students’ Verbal Communication in the English Education Study Program of the Tomakaka University of Mamuju. By answering these questions What kind of errors are made by students when committing verbal communication in the classroom at the English Education Study Program of the Tomakaka University of Mamuju? What are the causes of the errors? to achieve the aims, the researcher implemented research to analyse verbal communication by the Qualitative Descriptive method. This research was conducted at Tomakaka University Mamuju. English language students at Tomakaka Mamuju University, have many problems occurring at the same time In the framework of overcoming the problem, the researcher intends to carry out an analysis of the verbal communication of students. This analysis will be a reference to correct errors that often occur.